Experimental UWB channel characterisation of an electromagnetically small environment - Gelabert, J; Kavatjikidis, A; Edwards, D; Stevens, C (2009)
This paper presents an experimental characterization of the ultra-wide bandwidth (UWB) indoor channel based on an extensive measurement in a PC tower case environment to identify the optimum channel performance. The investigation is based on the analysis of the statistical properties of the multipath profiles, measured over a finely spaced measurement grid. The small-scale statistics of the received path energy follow Normal distributions with better time dispersion performance to be achieved with the existence of the Main Board (MB) on the measured channel. The Ricean K factor is examined to identify the multipath behavior of the channel. Finally, the channel capacity is calculated for three different transmitter levels with two different antenna polarization modes. A maximum channel capacity of 6.24 Gbps is achieved using the whole UWB band with a signal to noise ratio (SNR) of 10 dB with the main board present. Results show a significant reduction in overall channel capacity when antennas parallel to the main board plane are used. © 2009 IEEE.